A single nucleotide substitution in TaHKT1;5‐D controls shoot Na+ accumulation in bread wheat. (22nd July 2020) - Borjigin, Chana; Schilling, Rhiannon K.; Bose, Jayakumar; Hrmova, Maria; Qiu, Jiaen; Wege, Stefanie; Situmorang, Apriadi; Byrt, Caitlin; Brien, Chris; Berger, Bettina; Gilliham, Matthew; Pearson, Allison S.; et al.
Abstract: Improving salinity tolerance in the most widely cultivated cereal, bread wheat ( Triticum aestivum L.), is essential to increase grain yields on saline agricultural lands. A Portuguese landrace, Mocho de Espiga Branca accumulates up to sixfold greater leaf and sheath sodium (Na + ) than two Australian cultivars, Gladius and Scout, under salt stress in hydroponics. Despite high leaf and sheath Na + concentrations, Mocho de Espiga Branca maintained similar salinity tolerance compared to Gladius and Scout. A naturally occurring single nucleotide substitution was identified in the gene encoding a major Na + transporter TaHKT1;5‐D in Mocho de Espiga Branca, which resulted in a L190P amino acid residue variation. This variant prevents Mocho de Espiga Branca from retrieving Na + from the root xylem leading to a high shoot Na + concentration. The identification of the tissue‐tolerant Mocho de Espiga Branca will accelerate the development of more elite salt‐tolerant bread wheat cultivars. Abstract : A bread wheat ( Triticum aestivum L.) landrace Mocho de Espiga Branca maintained similar salinity tolerance compared to commercial cultivars despite accumulating high leaf sodium. An impaired sodium transporter TaHKT1;5‐D was shown to be responsible for the increased shoot sodium in this landrace.